2011
DOI: 10.3892/ijo.2011.1311
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule associated tumor suppressor 1 deficient mice develop spontaneous heart hypertrophy and SLE-like lymphoproliferative disease

Abstract: The microtubule associated tumor suppressor gene 1 (MTUS1) is a recently published tumor suppressor gene, which has also been shown to act as an early component in the growth inhibitory signaling cascade of the angiotensin II type 2 receptor (AT2R). In this study we report the generation of MTUS1 knock-out (KO) mice, which develop normally but reveal higher body weights and slightly decreased blood pressure levels. Twenty-eight percent of the studied MTUS1 KO mice also developed heart hypertrophy and 12% devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Recently, Zuern et al revealed that systemic Mtus1 knockout mice, lacking all splice variants, exhibited renal disease, lymphoid hyperplasia, and cardiac hypertrophy. 35 This cardiac phenotype agreed with the present observation; however, because renal diseases are usually associated with cardiac hypertrophy, it is still unclear whether Mtus1 ablation is directly related to cardiac hypertrophy. Moreover, the authors did not clarify which variants affected those phenotypes.…”
Section: Mtus1asupporting
confidence: 92%
“…Recently, Zuern et al revealed that systemic Mtus1 knockout mice, lacking all splice variants, exhibited renal disease, lymphoid hyperplasia, and cardiac hypertrophy. 35 This cardiac phenotype agreed with the present observation; however, because renal diseases are usually associated with cardiac hypertrophy, it is still unclear whether Mtus1 ablation is directly related to cardiac hypertrophy. Moreover, the authors did not clarify which variants affected those phenotypes.…”
Section: Mtus1asupporting
confidence: 92%
“…MTUS1 deficiency is implicated in multiple types of cancers. It reportedly plays important roles in vascular remodeling (12), adipocyte differentiation (13), lymphocytosis, and cardiac hypertrophy (14,15). We recently reported that MTUS1 transcript variant 5 is the most abundant isoform in ECs, and the loss of MTUS1 resulted in cAMP response element-binding protein (CREB) binding protein (CREBBP)-mediated NF-kB activation in ECs (16).…”
mentioning
confidence: 99%
“…Therefore, we examined in this study the expression of ATIPs during mouse development. To determine the histological location of Mtus1 expression during mouse development, beta‐galactosidase stainings of a gene‐trapped Mtus1 mouse line (Zuern et al, ) were performed (Figs. ).…”
Section: Resultsmentioning
confidence: 77%
“…Since Mtus1 is abundantly expressed during cardiovascular development, we would expect severe cardiac malformations and early lethality in Mtus1 knockout mice. However, this is not the case (Zuern et al, ), suggesting that other factors are compensating for the loss of ATIP. One predestinated candidate for this is the Mtus2 gene product CAZIP (also designated TIP150 or KIAA0774 in chicken).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation